OPPORTUNITIES FOR APPLYING INTERNATIONAL FINANCIAL ACCOUNTING AND REPORTING STANDARDS IN UNDER THE GREEN ECONOMY CONDITIONS (Ustozlar uchun, 2025)
Abstract: In the era of increasing ecological consciousness and sustainable development, the green economy has become an integral part of global economic discussions. This article examines the potential of implementing International Financial Accounting and Reporting Standards (IFRS) within the framework of the green economy. Emphasis is placed on the alignment of financial accounting and reporting practices with sustainability principles, the challenges of transparency in environmental investments, and the integration of environmental performance metrics (such as carbon foot , energy efficiency , water usage waste generation and management , air and water quality indices, biodiversity impact and renewable energy usage )in financial statements. Additionally, the role of international accounting bodies like the Association of Chartered Certified Accountants (ACCA) in shaping the future of sustainable reporting is highlighted